Efikasi Diri Akademik Sebagai Strategi Pengembangan Pembinaan Penyesuaian Psikologis Santri di Pesantren - Muniroh, Alimul; Rifqi Qushoyyi Adiyatma; Lujeng Lutfiyah (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2024)
The academic self-efficacy of Madrasah-Aliyah (MA) students is a description of the form of psychological dynamics of students in self-adjustment in Islamic boarding schools. Academic self-efficacy is defined as an individual's belief in his or her ability to do assignments, to manage his own learning activities, to realize academic expectations, both academic expectations from himself and from others. This study aims to describe the dynamics of academic self-efficacy of MA students in self-adjustment in pesantren. The study uses a case study research design, in the process of collecting data the researcher uses observation, interview and documentation methods. The research uses data analysis techniques that reduce data, present data and draw conclusions or verification. The research was carried out at MA Tarbiyatut Tholabah Kranji Lamongan. The results of the study show that students at MA Tarbiyatut Tholabah Kranji Lamogan who have high self-efficacy tend to be more successful in adjusting to the pesantren environment. They showed the ability to manage their time well, which had an impact on discipline and efficiency in carrying out daily routines. In addition, strong self-efficacy improves their performance, as they carry out each task with seriousness and confidence, which results in optimal results